Identification of Candidate Genes and Regulatory Factors Underlying Intramuscular Fat Content Through Longissimus Dorsi Transcriptome Analyses in Heavy Iberian Pigs - Muñoz, María; García-Casco, Juan María; Caraballo, Carmen; Fernández-Barroso, Miguel Ángel; Sánchez-Esquiliche, Fernando; Gómez, Fernando; Rodríguez, María del Carmen; Silió, Luis (Frontiers in Genetics, 2018)
One of the most important determinants of meat quality is the intramuscular fat (IMF) content. The development of high-throughput techniques as RNA-Seq allows identifying gene pathways and networks with a differential expression (DE) between groups of animals divergent for a particular trait. The Iberian pig is characterized by having an excellent meat quality and a high content of intramuscular fat. The objectives of the present study were to analyze the longissimus dorsi transcriptome of purebred Iberian pigs divergent for their IMF breeding value to identify differential expressed genes and regulatory factors affecting gene expression. RNA-Seq allowed identifying ~10,000 of the 25,878 annotated genes in the analyzed samples. In addition to this, 42.46% of the identified transcripts corresponded to newly predicted isoforms. Differential expression analyses revealed a total of 221 DE annotated genes and 116 DE new isoforms. Functional analyses identified an enrichment of overexpressed genes involved in lipid metabolism (FASN, SCD, ELOVL6, DGAT2, PLIN1, CIDEC and ADIPOQ) in animals with a higher content of IMF and an enrichment of overexpressed genes related with myogenesis and adipogenesis (EGR1, EGR2, EGR3, JUNB, FOSB and SEMA4D) in the animals with a lower content of IMF. In addition to this, potential regulatory elements of these DE genes were identified. Co-expression networks analyses revealed six long non-coding RNAs (lncRNAs) (ALDBSSCG0000002079, ALDBSSCG0000002093, ALDBSSCG0000003455, ALDBSSCG0000004244, ALDBSSCG0000005525, ALDBSSCG0000006849) co-expressed with SEMA4D and FOSB genes and one (ALDBSSCG0000004790) with SCD, ELOVL6, DGAT2, PLIN1 and CIDEC. Analyses of the regulatory impact factors (RIFs) revealed 301 transcriptionally regulatory factors involved in expression differences, with five of them involved in adipogenesis (ARID5B, CREB1, VDR, ATF6 and SP1) and other three taking part of myogenesis and development of skeletal muscle (ATF3, KLF11 and MYF6). The results obtained provide relevant insights about the genetic mechanisms underlying IMF content in purebred Iberian pigs and a set of candidate genes and regulatory factors for further identification of polymorphisms susceptible of being incorporated in a selection program.